Stock Taking of Lithuania's Science, Technology and Innovation System - Thorn, Kristian (World Bank, Washington, DC, 2017)
This report documents the progress of Lithuania in science, technology and innovation (STI) in areas singled out by three major international reports prepared by the Norwegian Research Council (1996), the World Bank (2003) and the CREST-OMC panel (2007). The task was to summarize recommendations of these studies, report on the progress achieved to date and point to priorities for the future. From a low point in the mid-1990s the Lithuanian STI system has gradually strengthened. Funding for R&D has increased and Lithuanian research groups have stepped up their performance in terms of publication output and relevance. It is the opinion of the reviewers that marked progress is evident and visible with respect to the goals of the three reports. This development has indeed been very positive and shows the strong commitment for a continuous improvement of the basic framework conditions for R&D in Lithuania. Nonetheless challenges remain. In order to further the development of STI-policies in Lithuania the report offers new recommendations in four areas: oversight and governance, science base, R&D linkages, and increasing innovative capacity.